Achieving Universal Health Coverage in Low- and Middle-Income Countries: Challenges for Policy Post-Pandemic and Beyond - Kodali PB (Dove Medical Press, 2023)
Prakash Babu Kodali Department of Public Health and Community Medicine, Central University of Kerala, Kasaragod, Kerala, IndiaCorrespondence: Prakash Babu Kodali, Department of Public Health and Community Medicine, Central University of Kerala, Kasaragod, Kerala, 671320, India, Tel +91 8330963085, Email prakashkodali@cukerala.ac.inBackground: Achieving universal health coverage (UHC) is critical for ensuring equity, improving health, and protecting households from financial catastrophe. The COVID-19 pandemic derailed the progress made across primary health targets. This article aims to review the policy challenges to achieve UHC in a post-pandemic world.Methods: A narrative review of 118 peer reviewed and grey literature was conducted. A total of 77 published articles were identified using an electronic search in PubMed and Scopus and a bibliographic search of relevant literature. Another 41 Reports, websites, blogs, news articles, and data were manually sourced from international agencies (WHO, World Bank, IMF, FAO, etc.), government agencies, and non-government organizations.Findings: The challenges were identified and discussed under five broad findings: i) weak public health care systems ii) challenges to building resilient health systems, iii) health care financing and financial risk protection, iv) epidemiological and demographic challenges, and v) governance and leadership.Conclusion: LMICs in Africa and South Asia face significant challenges to achieving UHC by 2030. As countries recover from the pandemic's aftermath, significant investments and innovations are needed to ensure progress toward UHC. Efficient resource mobilization through internal accruals, international cooperation, and resource sharing is needed.Keywords: COVID-19, health systems, healthcare financing, primary health care, universal health coverage